Computer-based instrumentation system for temperature measurement using RTD in visual basic application - Muhammad Hasbullah, Rais (2008)
In temperature measurement, the need to get accurate and stable reading is crucial since it play major role to what we produce. Computer-based instrumentation system for temperature measurement is one way that can be used to measure temperature where the data from measurement process can be directly use for other purpose, such as calculation and data monitoring. The purpose of this project is to study about temperature measurement as well as to develop a system to ease the process of doing experiment. The system developed is named as RTD’s-Temp where it is more focus on how to save time during experiment and get more systematic result. Manual method in temperature measurement is taking the data manually before finish the other things. The system is developed as alternative to conventional way of doing experiment for subject BEE4523 – Industrial Instrumentation. From the existence of this system, hope user can get benefits from it. RTD’s-Temp is developed in window-based application, which can be operated in any personal computer (PC).